(untitled) (Bangladesh Pharmaceutical Journal, 2024)
Despite being a common public health problem, there are few population-based research available to learn about the epidemiology and management of gastrointestinal reflux disease (GERD) in Bangladesh. The tenacity of this study was to investigate the prevalence, potential predisposing factors, clinical representation, therapeutic management of GERD among the young Bangladeshi population along with their beliefs regarding the disease. A descriptive cross-sectional study was conducted during 13th June 2022 to 10th December 2022 among 925 individuals (16-35 years of age) from various parts of Bangladesh. A standardized online questionnaire in both English and the local language (Bengali) was utilized to collect all the desired data that were analyzed using either Microsoft Excel 2019 or, IBM SPSS Statistics, v26.0. The prevalence of GERD was 55.7% which was not significantly associated with different sociodemographic parameters. However, family history (Odds ratio (OR) = 2.512), irregular meal (OR = 1.527) and spicy/junk food (OR = 1.495) were significantly associated with GERD prevalence in binary logistic regression analysis. Heart burn (94.0%) and regurgitation (83.3%) were the major symptoms observed and the average number of symptoms was higher in patients with relevant family history (p < 0.0005). Omeprazole (42.5%) was the most used medication to treat GERD followed by other proton pump inhibitors and H2 blockers. Self-medication was practiced by 52.6% of the patients which was associated with duration of treatment (p < 0.0005). The study has found a high prevalence of GERD in Bangladesh. Family history, irregular meal and spicy/junk foods have been identified as potential risk factors and only half the participants had the right belief regarding the effectiveness of lifestyle modification against GERD. Further cohort studies are advised to solidify the findings of this study. Bangladesh Pharmaceutical Journal 27(1): 19-36, 2024 (January)